Stepping Up Women's STEM Careers in Infrastructure : Case Studies - Schomer, Inka (World Bank, Washington, DC, 2020)
Stepping Up Women's STEM Careers in Infrastructure: An Overview of Promising Approaches describes a variety of ways to level the pathway for women entering into and progressing in science, technology, engineering, and mathematics (STEM) employment within the infrastructure sectors—energy and extractives; water; transport; and digital development. It is composed of three volumes : Volume 1 distills the findings from an extensive literature review, a global stocktaking exercise, key informant interviews, and five case studies in order to provide World Bank Group project teams with insights that they can use to support women’s STEM careers in infrastructure at each stage of their careers—from initial attraction to the sectors and job recruitment, to retention within organizations, and advancement to managerial and leadership roles. The report is intended to underpin and expand the existing knowledge on gender equality issues, under the World Bank’s Energy Sector Management Assistance Program (ESMAP).The case studies featured form part of the insight captured in the associated report Stepping Up Women’s STEM Careers in Infrastructure: Case Studies (Volume 1). Volume 2 is composed of five case studies that describe a variety of contexts in which measures are being implemented to attract, recruit, retain, and advance women in science, technology, engineering, and mathematics (STEM) roles in the infrastructure sectors across Ethiopia, the Lao People’s Democratic Republic (Lao PDR), North Macedonia, Panama, and Solomon Islands. The first three case studies profiled in this document focus specifically on recruitment, retention, or advancement. The remaining two case studies focus on organizations that are tackling the issue of women’s underrepresentation holistically, in each of the crucial stages of a woman’s career. The case studies featured form part of the insight captured in the main report Stepping Up Women’s STEM Careers in Infrastructure: An Overview of Promising Approaches (Volume 1). Volume 3 summary note provides a brief overview of some of the findings from an extensive literature review, a global stocktaking exercise, key informant interviews, and five case studies (featured in Volume 1 and 2) in order to provide World Bank Group project teams with insights that they can use to support women’s STEM careers in infrastructure at each stage of their careers.